Exploring the meaning of ageing and quality of life for the sub-urban older people - Alavi, Khadijah; Md. Sail, Rahim; Mohamad, Mohd Suhaimi; Omar, Mustaffa; Subhi, Nasrudin; Chong, Sheau Tsuey; Sarnon @ Kusenin, Norulhuda; Ibrahim, Fauziah; Mohamad, Lukman @ Zawawi (Universiti Putra Malaysia Press, 2011)
A quality of life which includes psychological well-being, good physical functioning, relationships with others, health, and social activity is very important to the aged. The main purpose of this descriptive and exploratory case study was to analyze the meaning of aging and perceived quality of life among the elderly in sub-urban communities. Participants were 15 Malays, Chinese and Indians, aged 60 and above. In-depth interviews with the participants were conducted to gather the data. The findings indicated that aging brought a lot of shortfall, especially in terms of health and physical strength to the elderly. They were pleased to see the development of families, children, and grandchildren as a quality of life. Respondent are contented living with their children and grandchildren. The implication of this study is that there is a need for more gerontological social workers with adequate training and skills to provide services for the elderly.